Land Use Survey in Vlora - Childress, Malcolm (My University, 2001)
Land Use Survey in Vlora continues to be an initiative of the Land Policy Department of the Project Management Unit for the Immovable Property Registration System. Its main objectives have been the systematic observation of the urban landscape of Vlora during the transition period in Albania towards the Market Economy as well as the creation of the information basis for PMU in the first registration process in the urban zones.
24 p.
Keywords: Urban Land; Albania; Land Tenure Center; University of Wisconsin--Madison